Assess the level of farmers' awareness regarding climate changes and its impacts on agriculture in Sétif province (north-east Algeria) - Nasri Samir; Belabbas Messaoud; Bouzid Hamza (Glasnik Srpskog Geografskog Društva)
The present study presents the phenomenon of climate changes through discussing its impacts on agriculture productions in Sétif Province, which is area of survey that located in the high plains of north-east Algeria. The study focuses to evaluate the perception degree of peasants toward the phenomenon via statistical analysis and discuss its futures challenges. It is presumed that climate changes have a significant effect on agriculture in the region; the water usage was increased in agriculture and the expansion of saline areas has increase soil degradation. Still, the vegetable and fruit crops reporting negative impacts living organisms are experiencing imbalances in natural biodiversity. In other point, the findings indicate that over half of the participants farmers (63.00%) have a moderate level of knowledge about climate changes, while 18.04% have a high level of knowledge. The status of the agriculture is in a critical condition and the findings indicate a relative gap in understanding the climate changes. Based on, some challenges have been revealed mainly: highlighting the need for effective dissemination of agricultural recommendations to improve farmers' knowledge that can support adaptation and mitigation toward climate change effects. In parallel, the agriculture is in need of continuous follow-up survey in the context of climate changes and socio-economic aspect to assure the quality of life in rural area and guaranteeing food security, where the environmental perspectives and sustainable development should be considered in the future spatial planning.